Comparative Aspects of Scottish and Irish Economic and Social History, 1600-1900 - Akenson, Donald H. (Labour / Le Travail, 1980)
This article reviews the book, "Comparative Aspects of Scottish and Irish Economic and Social History, 1600-1900," by L.M. Cullen and T.C. Smout.